Evaluation of a Fixed-Angle Wedge Osteotomy Guide - Neal, Katherine M.; Frederick, Steven W.; Corse, Matthew R.; Cross, Alan R. (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The aim of this study was to evaluate a fixed-angle cutting guide designed to aid in the performance of coplanar wedge osteotomies using a proximal tibial cranial closing wedge ostectomy model.Study Design A 30-degree cranial closing wedge ostectomy was created using canine tibia models with either a standard template (method T) or a wedge osteotomy guide (method G) by two surgeons. One surgeon was experienced with both procedures, and one surgeon had no previous experience with the wedge guide. The ostectomy wedges were evaluated for wedge angle, using a digital protractor, and coplanarity by using digital photographs and screen-measuring software.Results The mean (standard deviation) wedge angles of the T and G groups were 28.16 (1.33) and 28.4 degrees (1.46) respectively. The mean (standard deviation) divergence angles of the T and G groups were 3.21 (1.86) and 2.22 degrees (1.69) respectively. The measured reference angles of the template and cut guides were 31.27 and 29.60 degrees respectively. Individual and cross-surgeon analysis of outcomes found no significant differences when comparing wedge angle or coplanarity with either method regardless of surgeon experience. However, mean wedge angle of group G was significantly closer to the measured reference angles than group T (p < 0.01).Conclusion Use of a fixed-angle surgical wedge guide was successful in consistently producing accurate closing wedge ostectomies regardless of surgeon experience. These results show that use of the guide is a valid method for performing wedge ostectomies.
Keywords: wedge osteotomy; deformity correction; corrective osteotomy; osteotomy guide